PENGARUH KEMAMPUAN KOMUNIKASI TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA PT.BRI (PERSERO) CABANG PALANGKA RAYA - Mahrawati Mahrawati (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2020)
Human resources will determine on the success of company activity implementation. There is an increasing urgent need for companies to obtain, develop and maintain qualified human resources in accordance with always changing environmental dynamic. This research aims to (1). To determine the influences of communication and leadership ability on the effectiveness of employees at PT. BRI (Persero) Branch of Palangka Raya (2).To find out the variable with the most dominant influence on employee effectiveness at PT. BRI (Persero) Branch of Palalangka Raya.This research was conducted at the Office of PT. BRI Branch of Palangka Raya on A. Yani Street as the research objects are the employees who work at PT. BRI Branch of Palangkaraya. Based on the partial test conducted on the variables included in the analysis model, it can be seen that both research variables, namely Communication variable (X1) of 0.377, and organizational culture (X2) of 0.363, which simultaneously have influence and significance on the effectiveness of employee working at PT. BRI Branch of Palangkaraya. Similarly, if seen partially, it is known that both variables have positive and significant influences. The communication ability performed by the employees serves as the most dominant variable on the work effectiveness of employees of PT. BRI Branch of Palangkaraya which could be seen from the amount of influence namely by 37.7%.